SAT0336 Malnutrition and sarcopenia in a large cohort of patients with systemic sclerosis. (15th June 2017) - Caimmi, C; Caramaschi, P; Venturini, A; Bertoldo, E; Ferrari, M; Rossini, M
Abstract : Background: Systemic sclerosis (SSc) is an autoimmune disease that may affect gastrointestinal tract, leading to malabsorption and malnutrition. Previous studies defined this complication with no widely accepted criteria. No thorough evaluations of sarcopenia are available. Methods: 141 SSc consecutive outpatients have been enrolled. A thorough history, blood samples and body composition by densitometry were collected. Malnutrition was defined accordingly to recently published and widely accepted ESPEN criteria (1); sarcopenia was diagnosed in patients with a reduced skeletal muscle index (2). Results: The table summarizes cohort's characteristics. Malnutrition was diagnosed in 9.2% (CI95%: 4.4–14.0%). Malnourished patients were more often treated with steroids (p=0.039), had worse gastrointestinal symptoms accordingly to UCLA questionnaire (p=0.007), lower physical activity accordingly to International physical activity questionnaire (p=0.028), longer disease duration (p=0.019), worse predicted DLCO/VA and FVC (p=0.009, respectively) and worse disease severity accordingly to Medsger severity score (DSS) (p<0.001 for total, p=0.001 for lung and p<0.001 for gastrointestinal tract). In multivariate analysis only FVC (p=0.006) and disease severity (p=0.003), in particular lung involvement as defined by DSS (p=0.013), were confirmed to be worse in malnourished patients. Z-scores were significantly lower in malnourished patients at lumbar site p=0.033), even after correcting for possible confounders. Sarcopenia was diagnosed in 20.7% (CI95% 14.0–27.4%); 11/29 sarcopenic patients were also malnourished and 6/29 were cachectic (i.e. sarcopenia + systemic inflammation). Sarcopenic patients had worse DLCO/VA (p=0.003) and lung (p=0.005) involvement accordingly to DSS than non-sarcopenic ones; cachectic had even lower value (p=0.016 for both). Sarcopenic patients had also longer disease duration (p=0.033). Conclusions: Malnutrition defined with widely accepted diagnostic criteria was found to be lower than previously reported (3–7) using screening tool or non-validated criteria. Sarcopenia was found to be somewhat common, although no previous study on comparable cohorts are available. Lung involvement and function was shown to be significantly linked with nutritional status and may not be explained only by muscle weakness given the absence of correlation between muscle weakness and FVC but only with DLCO/VA. References: Cederholm et al. Clinical Nutrition 2015;34;335. Baumgartner et al. Am J Epidemiol 1998; 147:755. Baron et al. J Rheumatol 2009;36:2737. Krause et al. Ann Rheum Dis 2010;69:1951. Murtaugh et al. Clin Nutr 2013;32:130. Caporali et al. Clin Nutr 2012;31:666. Rosato et al. Nutrition 2014;30:204. Disclosure of Interest: None declared